AB0830 LIPID PROFILE IN PSORIATIC ARTHRITIS. FREQUENCY AND ASSOCIATION WITH DISEASE ACTIVITY. (2nd June 2020) - Savio, V.; Tissera, Y.; Quaglia, M. I.; Albiero, J. A.; Alonso, C. G.; Demarchi, M.; Maldini, C.; Gobbi, C.; Yorio, M.; Martini, A. C.; Castrillon, M. E.; Alba, P.
Abstract : Background: Psoriatic arthritis (PsA) is a chronic inflammatory disease associated with higher risk of cardiovascular events and metabolic syndrome. The inflammation not only accelerates atherosclerosis, but also may influence cardiovascular (CV) risk factors such as lipid profile, blood pressure and insulin resistance. Lipid profile has previously been studied in PsA, however this association is still controversial. Objectives: To study the frequency of altered lipid profile in patients with PsA and its association with disease activity. Methods: We studied all the patients with diagnosis of PsA who consecutively attended to Rheumatology Unit at Cordoba Hospital from July 2018 to December 2019. PsA was diagnosed according CASPAR criteria. Clinical and laboratory data were collected. The activity of the disease was evaluated by PASI, MDA and DAPSA. Quantitative variables will be expressed in median and 1st and 3rd interquartile; qualitative variables expressed in frequency and percentage. Correlation analysis was calculated using Spearman's rank correlation coefficient. P<0.05 was considered statistically significant. Results: 42 PsA patients were included. Mean age was 56 years old (47.25-62.75) and 54.76% were female (n=23). 92.86% (n=39) of the patients had plaque Psoriasis and 87.8% (n=36) had peripheral joint involvement. Frequency of comorbidities in PsA are shown in Graphic 1. 31 (73.8%) of the patients were treated with topical therapy, 3 (7.14%) with phototherapy, 31 (73.8%) with Methotrexate and 17 (41.46%) with biologics and JAK inhibitor. Activity Disease Index and Lipid profile are shown in Table 1 and 2. There was not association between Apo B/Apo A coefficient with DAPSA (rho=0.013; p=0.940) and MDA (rho=-0.029; p=0.867). Conclusion: In spite of the presence of cardiovascular factors in the majority of PsA patients, lipid profile is not correlated with disease activity in this population. References: [1]Ahlehoff O, Gislason GH, Charlot M, et al. Psoriasis is associated with clinically significant cardiovascular risk: A Danish nationwide cohort study. J Intern Med 2011;270:147-57. [2]Mallbris, L., Ritchlin, C.T., Ståhle, M. "Metabolic disorders in patients with psoriasis and psoriatic arthritis." Curr RheumatolRep.8(5): 355–363. 2006 [3]Ng CY, Tzeng I-S, Liu S-H, Chang Y-C, Huang Y-H. Metabolic parameters in psoriatic patients treated with interleukin-12/23 blockade (Ustekinumab). J Dermatol 2018; 45:309–313 [4]Kaur S, Kingo K, Zilmer M. Psoriasis and cardiovascular risk – do promising new biomarkers have clinical impact? Mediators Inflamm 2017; 2017: 7279818 [5]Gentile M, Peluso R, Di Minno MN, et al. Association between small dense LDL and sub-clinical atherosclerosis in patients with psoriatic arthritis. ClinRheumatol 2016; 35: 2023-9. Disclosure of Interests: None declared